Academic Achievement in Adults with a History of Childhood Attention-Deficit/Hyperactivity Disorder: A Population-Based Prospective Study. Issue 1 (January 2017) - Voigt, Robert G.; Katusic, Slavica K.; Colligan, Robert C.; Killian, Jill M.; Weaver, Amy L.; Barbaresi, William J.
ABSTRACT: Objective: Previous research on the developmental course of attention-deficit/hyperactivity disorder (ADHD) is limited by biased clinic-referred samples and other methodological problems. Thus, questions about adult academic outcomes associated with childhood ADHD remain unanswered. Thus, the objective of this study was to describe academic outcomes in adulthood among incident cases of research-identified childhood ADHD versus non-ADHD referents from a population-based birth cohort. Method: Young adults with research-identified childhood ADHD (N = 232; mean age 27.0 yr; 72.0% men) and referents (N = 335; mean age 28.6 yr; 62.7% men) from a 1976 to 1982 birth cohort (N = 5699) were invited to participate in a followup study and were administered an academic achievement battery consisting of the basic reading component of the Woodcock-Johnson III Tests of Achievement (WJ-III) and the arithmetic subtest of the Wide Range Achievement Test—Third Edition (WRAT-3). Outcomes were compared between the 2 groups using linear regression models, adjusted for age, sex, and comorbid learning disability status. Results: Childhood ADHD cases scored from 3 to 5 grade equivalents lower on all academic tests compared with referents, with mean (SD) standard scores of 95.7 (8.4) versus 101.8 (8.1) in basic reading; 95.0 (9.3) versus 101.9 (8.5) in letterword identification; 98.2 (8.6) versus 103.2 (9.2) in passage comprehension; 95.7 (9.1) versus 100.9 (9.0) in word attack; and 87.8 (12.9) versus 98.0 (12.0) in arithmetic. Conclusion: This is the first prospective, population-based study of adult academic outcomes of childhood ADHD. Our data provide evidence that childhood onset ADHD is associated with long-term underachievement in reading and math that may negatively impact ultimate educational attainment and occupational functioning in adulthood.